2021
DOI: 10.54090/alulum.106
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Guru Pendidikan Agama Islam Dalam Membina Akhlak Peserta Didik

Abstract: This study aims to determine the efforts of Islamic Religious Education teachers in fostering the morals of students. This study uses a qualitative research type with the subject of class VIII students, as informants for PAI teachers, school principals, curriculum sections and counseling teachers at SMP Muhammadiyah 1 Sukoharjo. Data were taken using observation, interviews and documentation. While the data analysis by data reduction, data presentation and data verification. The results of this study are the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
5
0
3
Order By: Relevance
“…Praying together according to each religion and belief is a form of mutual respect between people for different religions and beliefs (Marintan & Priyanti, 2022). Greeting is the duty of a Muslim toward other Muslims (Rosyidah, 2019). Praying is a form of applying religious values because prayer is one of the acts of worship that must be performed before carrying out activities such as studying (Kurniawan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Praying together according to each religion and belief is a form of mutual respect between people for different religions and beliefs (Marintan & Priyanti, 2022). Greeting is the duty of a Muslim toward other Muslims (Rosyidah, 2019). Praying is a form of applying religious values because prayer is one of the acts of worship that must be performed before carrying out activities such as studying (Kurniawan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…From the previous research presented above, it can be concluded that the use of punishment in improving the discipline of students in Islamic boarding schools is considered important for forming discipline and positive character (Azizah et al, 2021). This research also aims to create a more disciplined and conducive Islamic boarding school environment with the help of implementing educational punishments that are adjusted to Islamic norms.…”
Section: Fourthly Research Entitled Analysis Of Character Education S...mentioning
confidence: 92%
“…In this case, the author will also provide a description related to the solution that has been formulated using descriptive techniques. The products that have been developed are only described based on current needs in the world of education and have not yet reached the content or content validity stage (Engkizar et al, 2018;Oktavia et al, 2023).…”
Section: Methodsmentioning
confidence: 99%